Eksistensi Hukum Pidana Adat dalam Rancangan KUHP: Problematika Asas Legalitas dan Over-Kriminalisasi - Arrasuli, Beni Kharisma (UNES Law Review, 2023)
This article discusses the dynamics of customary criminal law in the Draft Criminal Code (RKUHP), this is because the RKUHP is currently codifying customary criminal law in its regulations. Of course, this arrangement regarding the adherence to customary criminal law reaps pros and cons in the community, because the Criminal Code (KUHP) previously did not understand the existence of the phrase customary criminal law in its formulation of offenses. It is considered that the embodiment of customary criminal law in the RKUHP will cause problems with the principle of legality and can cause over-criminalization of the community, especially those in the customary law area. The enactment of customary criminal law in the RKUHP should be able to shift the meaning of the principle of legality which is a fundamental principle in Indonesian criminal law and does not rule out the possibility that the enactment of Article 2 paragraphs (1) and (2) of the Criminal Code will lead to a high quantity of criminalization in Indonesia. So a comprehensive study is needed to fix the problems of customary law offenses contained in the RKUHP, This aims not to cause misunderstandings for the community and to prevent confusion in understanding the purpose of a legal product renewal.